Investigating lipopolysaccharide-induced inflammation in Sprague-Dawley rats on liver function with specific focus on coagulation factor production - Bester, Janette (University of Pretoria, 2023)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2023.